The Influence Of Certification, Competence, Education, Discipline, And Work Motivation On The Performance Of Kindergarten Heads In Islamic Kindergartens Throughout The City Of Serang. - nursalim nursalim; Abdul Gofur Ahmad; Herwina Bahar (Journal Of Social Science (JoSS), 2024)
This study aims to investigate the influence of certification, competence, education, discipline, and work motivation on the performance of kindergarten heads. This research is included in survey-type research and is quantitative. The collected data were analyzed quantitatively. The analysis method used in this research is the Structural Equation Model (SEM) using the SmartPLS 4.0 application. The results obtained in the validity test state the loading factor value ? 0.7 and the AVE value ? 5 so that it can be declared valid, in the composite reliable test and Cronbach alpha ? 0.7 so that it can be declared reliable. The results showed that the certification variable (X1) had a positive and significant influence on the discipline variable (Z1). The certification variable (X1) has a positive and significant influence on the work motivation variable (Z2). The certification variable (X1) has a positive and significant influence on the performance variable (Y). The competency variable (X2) has a positive and significant effect on the discipline variable (Z1). The competency variable (X2) has a positive and significant influence on the work motivation variable (Z2). The competency variable (X2) has a positive and significant effect on the performance variable (Y). The education variable (X3) has a positive and significant effect on the discipline variable (Z1). The education variable (X3) has a positive and significant influence on the work motivation variable (Z2). The education variable (X3) has a positive and significant influence on the performance variable (Y).